Involvement of RAGE in radiation-induced acquisition of malignant phenotypes in human glioblastoma cells - Seki, Hiromu; Kitabatake, Kazuki; Tanuma, Sei-ichi; Tsukimoto, Mitsutoshi (Biochimica et biophysica acta. General subjects, 2024)
Glioblastoma (GBM), a highly aggressive malignant tumor of the central nervous system, is mainly treated with radiotherapy. However, since irradiation may lead to the acquisition of migration ability by cancer cells, thereby promoting tumor metastasis and invasion, it is important to understand the mechanism of cell migration enhancement in order to prevent recurrence of GBM. The receptor for advanced glycation end products (RAGE) is a pattern recognition receptor activated by high mobility group box 1 (HMGB1). In this study, we found that RAGE plays a role in the enhancement of cell migration by γ-irradiation in human GBM A172 cells. γ-Irradiation induced actin remodeling, a marker of motility acquisition, and enhancement of cell migration in A172 cells. Both phenotypes were suppressed by specific inhibitors of RAGE (FPS-ZM1 and TTP488) or by knockdown of RAGE. The HMGB1 inhibitor ethyl pyruvate similarly suppressed γ-irradiation-induced enhancement of cell migration. In addition, γ-irradiation-induced phosphorylation of STAT3 was suppressed by RAGE inhibitors, and a STAT3 inhibitor suppressed γ-irradiation-induced enhancement of cell migration, indicating that STAT3 is involved in the migration enhancement downstream of RAGE. Our results suggest that HMGB1-RAGE-STAT3 signaling is involved in radiation-induced enhancement of GBM cell migration, and may contribute to GBM recurrence by promoting metastasis and invasion. [Display omitted] •γ-Radiation induces enhanced migration of human glioblastoma cells.•RAGE and RAGE ligands are involved in radiation-induced cell migration.•STAT3 signaling is involved in radiation-induced cell migration.•Radiation-induced phosphorylation of STAT3 is mediated by RAGE.•HMGB1-RAGE-STAT3 signaling is involved in radiation-enhanced cell migration.